What Do Statistical "Demand Curves" Show? - Working, E. J. (Quarterly Journal of Economics, 1927)
How statistical demand curves are constructed, 213. — The theory of the demand-and-supply curve analysis applied to a period of time, 217. — Statistical curves which would result under hypothetical conditions, 218. — Data used do not necessarily reflect influence of demand more than of supply, 222. — Whether fitted curve approximates a demand or supply curve depends on the relative variability of demand and supply, 224. — Slope of the fitted curve may not correspond to the true demand curve, 225. — In what sense may statistical demand curves be "general" demand curves? 228. — Distinction between consumer and dealer demand, 230. — Fitted curves are "static" in the sense of showing an "average" relationship, or relationship at a "typical" point of time, 231. — Do statistical demand curves assume all other things equal? 233. — Conclusions, 234.